Necesidad de reformar el art. 25 y 26 de la ley orgánica de regulación y control del poder de mercado, en relación a las sanciones de prácticas desleales - Tapia Paredes, Maybety del Rosario (2014)
The first paragraph of Article 26 of Law for the Regulation and Control of Market Power states that: "It is forbidden and will be punished in terms of this Act, the acts or unfair practices, whatever form they take and whatever economic activity they are manifested, where they prevent, restrict, falsify or distort competition, undermine economic efficiency, or general welfare or the rights of consumers and users." This rule determines that an unfair act may be punished by any means take the appropriate authorities, ie the existence of actual damage is indicated, as these authorities have the power to decide which company can and that companies can not be the market, distorting free competition and creating risks in the national and international market. As this article indicates that they will be punished in terms of this Act, the acts or unfair practices, whatever form it takes and whatever economic activity they are manifested, it is determined that unfair competition is a tort because the test data should be penalized for not more damage negligently, and that test data must be submitted only in case of obtaining veterinary products that produce chemicals, such as stated in Article 27 section 5 letter c) of the Law for the Regulation and Control of Market Power , but not of chemical products they create. An unfair act should be punished if they neglect ie there must be awareness and willingness of the acts, as the market is distorted when damage exists and when the will is latent damage.